Effect of Chia Flour Incorporation on the Nutritive Quality and Consumer Acceptance of Chips - Coorey, Ranil; Grant, Alexandra; Jayasena, Vijay (Canadian Center of Science Education, 2012)
Gluten free, antioxidant, calcium and dietary fibre rich, chia is known to contain the highest level of omega-3 available in any cultivated plant source. The objective of this research was to develop a high protein, high dietary fibre, gluten free and omega-3 fatty acid rich chips. Four different levels of whole chia flour (5%, 10%, 12%, and 15%) were incorporated to produce chia chip. There were no significant differences in appearance, colour, flavour and overall liking between a commercial chip sample and the 5% chia chips. The chemical analysis indicated that all four trial chips are excellent sources of omega-3 and the baking process has a limited impact on their nutritional profile. For optimal consumer acceptance and nutritional benefits, the incorporation of 5% chia is recommended. With limited chia based food products currently available, a chia chip would be a well-accepted and healthy alternative to the common unhealthy chips.